2005
DOI: 10.5271/sjweh.859
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for persistent elbow, forearm and hand pain among computer workers

Abstract: The following article refers to this text: 2008;34(2):81-164

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
5
44
0
2
Order By: Relevance
“…Repetitive strains, bruising and lacerations were reported as the most common types of injury which is also consistent with previous studies (Dufort et al, 1997;Lassen et al, 2005;Taylor et al, 2004). Most repetitive strain injuries can be prevented by adequate health promotion and injury prevention strategies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Repetitive strains, bruising and lacerations were reported as the most common types of injury which is also consistent with previous studies (Dufort et al, 1997;Lassen et al, 2005;Taylor et al, 2004). Most repetitive strain injuries can be prevented by adequate health promotion and injury prevention strategies.…”
Section: Discussionsupporting
confidence: 91%
“…It is suggested that a valid approach to the measurement of LBP be designed so that occupational physiotherapists can systematically document the outcome of the clinical interventions applied and compare these results against any significant changes of future interventions (Bardin, 2002) The upper limb and spine/trunk accounted for permanent injuries. The upper limbs are consistently reported as the most vulnerable site for permanent injuries (Lassen et al, 2005;Mell et al, 2005) due to the functional role they frequently play in manipulative skills. As such, it is likely that serious injury does develop as a result of accidents and cumulative trauma or other factors leading to serious or permanent injury.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric measures such as differences in shoulder width and hand size have also been proposed as possible factors increasing the ris for women (Karlqvist et al, 1998;Tittiranonda et al, 1999). One study of risk factors among computer users indicated that pain in other body regions was a predictor of persistent arm pain (Lassen et al, 2005). Moreover, constitutional o acquired vulnerability (biological or psychological) as well as socioeconomic factors may have an impact on the risk of developing musculoskeletal symptoms/disorders in connection with computer work (Cole and Rivilis, 2004 In a cross-sectional study, work style was identified as a possible risk factor for n (Feuerstein et al, 1997).…”
Section: Inmentioning
confidence: 99%
“…S computer work and neck/upper extremity symptoms or disorders Cook et al, 2000;Jensen et al, 1998;Karlqvist et al, 2002), and several recent longitudinal studies have supported these cross-sectional findings (Gerr et al, 20 Jensen, 2003;Juul-Kristensen et al, 2004;. However, another longitudinal study concluded that the duration of computer use did not influence the prognosis of persistent pain in the arm or hand region of the subje (Lassen et al, 2005). Moreover, it concluded that self-reported exposures associated with time spent using the mouse and the keyboard could predict pain or symptoms of the elbow/wrist/hand for low-level exposure, but could not predict clinical conditions verified through medical examinations (Lassen et al, 2004).…”
mentioning
confidence: 94%
See 1 more Smart Citation